A stochastic approach for blockchain Internet of Things integration - Khalifa, Othman Omran; Ahmed, Muhammed Z.; Saeed, Rashid A; Kida, Aliyu Musa; Albagoul, Abdul Gani; Esgiar, Abdelrahim N (Institute of Electrical and Electronics Engineers Inc., 2022)
The ease of adaptability of Internet of Things (IoT) enables multiple devices to communicate with the aim of shearing data and information resources. The IoT architecture of operation is by default centralized. However, the distributed and decentralized architecture of Blockchain enables efficient and scalable connectivity between conventional devices and IoT devices. A Blockchain is considered as a technology with a distributed ledger that enables data transactions with integrity. In this paper, an analysis of the benefits and drawbacks of integrating IoT and Blockchain technology is efficiently conducted. A problem is formulated to analyze the system model by considering both internal and external attacks on a network. Also, a security analysis is conducted by formulating equations. Use-case analysis is proposed to seamlessly locate an IoT device and ensure access control for inbound and outbound link throughout the IoT system. In our results, MATLAB2019b is used in presenting graphical results for compromised node, cooperative nodes, and total number of node count. This analysis is conducted using stochastic approach to determine successful defense for node attach in percentage counts.